An investigation of (2+1)-dimensional asymmetric Nizhnik-Novikov-Veselov system: Lie symmetry reductions, invariant solutions, dynamical behaviors and conservation laws - Kumar, Sachin; Kumar, Amit; İnç, Mustafa; Alotaibi, Hammad; Abdou, M. A.; Akguel, Ali (Elsevier, 2022)
In this study, we develop the asymmetric Nizhnik-Novikov-Veselov (ANNV) system in (2+1)-dimensions, which has applications in processes of interaction of exponentially localized wave structures, as well as the infinitesimal generators, Lie symmetries, vector fields, and the commutator table. The link between Lie symmetry vectors and conserved vectors is constructed using symmetry conservation principles once Lie point symmetries are first deduced. Using the aforementioned Lie symmetry technique, two-stage symmetry reductions are used to obtain the precise analytical answers. These analytical solutions all incorporate a number of different functional parameters as well as arbitrary constant parameters. The diversity of the physical phenomena of the obtained soliton solutions is illustrated by the inclusion of arbitraryness of functional parameters and constants. By using Noether's method, conservation laws have subsequently been attained. The innovative aspect of the work described in this paper is an attempt to use 3-dimensional and 2-dimensional visuals, along with appropriate arbitrary parameter selections and functional parameter values, to represent the dynamical behavior of the solutions that have been produced. In order to make this research more intriguing, stripe solitons, dark-bright solitons, solitary waves, singular wave-form soliton, and other types of soliton wave profiles of the achieved solutions are described. The effectiveness, benefits, and utility of the employed approach are demonstrated by the physical and graphical interpretation of the answers attained.
Keywords: Closed-form solutions; Lie symmetries; Infinitesimal generators; ANNV equation; Solitary waves